Rare and Treatable Cause of Early-Onset Refractory Absence Seizures - Panandikar, Gajanan A. (J Pediatr Neurosci, 2018)
Glut-1 transporter deficiency syndrome (GLUT1-DS) is a rare disorder caused by the mutation in SLC2A1 gene, which results in impaired glucose transport into the brain. It has a broad spectrum of phenotypic presentation ranging from cognitive decline, microcephaly, and refractory seizures to complex movement disorder. Recognition of this disorder is necessary as it is refractory to antiepileptic drugs (AEDs) and responds significantly to ketogenic diet. We report a case of 7-year-old girl who presented with paroxysmal eye movements in infancy with early-onset absence epilepsy (EOAE), which worsened in early morning and on fasting and was found to be refractory to four AEDs. She had mild developmental delay and subtle ataxia. Cerebrospinal fluid showed hypoglycorrhachia, and molecular analysis identified deletion in exon 4 of SLC2A1 gene (p.leu169del), thus confirming GLUT1-DS. She had a near-complete seizure control on ketogenic diet. Thus, GLUT1-DS should be suspected in all cases of refractory generalized seizures specially EOAE, especially if it worsens on fasting, is associated with development delay, positive family history, or paroxysmal movement disorder.